PENERAPAN APLIKASI MANAJEMEN KEUANGAN DI SMK TELADAN KERTASEMAYA - Marjani Santosa, Yaqutina; Nugraha, Nur Budi; Muhamad, Fachrul PB (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2024)
Indramayu State Polytechnic (POLINDRA) is obliged to organize the Tridharma of Higher Education (education, research, and community service). Where lecturers (teaching staff) are required to carry it out. One of the mandatory implementations is community service. The results of community service can be in the form of applying, practicing, and cultivating science and technology to advance general welfare and educate the nation's life; and solving problems faced by the community by utilizing the expertise of relevant academic communities, the use of appropriate technology, science and technology development materials or teaching materials or training modules for the enrichment of learning resources.After making observations and interviews with the principal of SMK Teladan Kertasemaya, Mrs. Khoirun Nisa, S.Si, it was found that the problem in the form of an honorarium system in schools still uses a manual system. Manual systems often cause errors in the system due to human error and calculation problems. So a digitized system is needed so that these errors can be minimized. To overcome the problems that occur, a solution is proposed in the form of developing financial management applications in the school. In application development using website-based applications